The Effect of Electronic Marketing on International Trade: case study on Algerian International Companies - Boussalem, Aboubaker (Finance and Business Economies Review, 2022)
This study investigates the influence of e-marketing mix components on the success of international firms in Algeria, as well as the relationship between e-marketing mix parts and individual performance. First, A model was built and hypotheses were supplied to meet the study's objectives. A standardized questionnaire prepared expressly for this study was used to collect data from Algerian enterprises' marketing and management teams. A Multiple regression study revealed that e-marketing mix elements have a significant influence on business performance. Simple regression analysis revealed that each component of the e-marketing mix has a significant influence on the performance of international companies doing business in Algeria. Also, The elements of the e-marketing mix (promotion, product, location, and pricing) were shown to have a positive influence on the operations of international companies operating in Algeria. Therefore, Algerian companies are advised to apply this technology in their international market to cope with the international advancement in technology and the internet. Finally, research conclusions, results, and recommendations are outlined